Analisis Aplikasi Mfin Terhadap Kepuasan Karyawan Pt.Mandala Multifinance, Tbk Dengan Framework Customer Satisfaction Index (Csi) - Abdul Rahmadan Haeradi; Adi Hermawansyah; Nuorma Wahyuni (Jurnal Indonesia Sosial Teknologi, 2022)
The MFIN application has an extensive impact in their day by day work to make it more straightforward for representatives, in view of the aftereffects of starting perceptions on the MFIN application, a sign of issues in the MFIN application is as yet encountering blunders, program refreshes don't have a manual, so mistakes regularly happen. So it is important to examine representative fulfillment with the MFIN application. This review means to investigate the MFIN application on worker fulfillment at PT. Mandala Multifinance, Tbk. This exploration was directed in a few branches and the example in this review were representatives of PT. Mandala Multifinance, Tbk. The strategy utilized in this review is the Consumer loyalty File (CSI). In light of the aftereffects of information handling and examination that has been done, it tends to be inferred that the reports or issues that exist in PT. Mandala Multifinance, Tbk to the MFIN application, not every one of them are right founded on the aftereffects of information handling that has been completed there is an interest or assumption with an exceptionally fulfilled classification, we can know from the CSI esteem got a figure of 86.76% dependent on the CSI File table is delegated generally excellent . This implies that most workers are extremely happy with the MFIN application.